2013
DOI: 10.5815/ijigsp.2013.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Mass Detection in Lung CT Images Using Region Growing Segmentation and Decision Making Based on Fuzzy Inference System and Artificial Neural Network

Abstract: Abstract-Nowadays, Karyotype analysis is frequently used in cytogenetics. It is a time-consuming and repetitive work therefore an automatic analysis can greatly be valued. In this research, an automatic method is presented. Firstly, a proposed locally adaptive thresholding method is used to segment chromosome clusters. Then, the clusters is divided into two main categories including, single chromosomes and multichromosome clusters based on geometric shape of clusters. In the next step, each extracted cluster i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
(24 reference statements)
0
18
0
1
Order By: Relevance
“…Since then, the ANFIS method has been widely used in many research areas, such as prediction (Abdulshahed, Longstaff, & Fletcher, ; Hegde & Raju, ; Petković, Shamshirband, Abbasi, Kiani, & Al‐Shammari, ; Rai, Pai, & Rao, ), knowledge discovery (Huang, Tsou, & Lee, ; Inyang & Akinyokun, ; Vahidnia, Alesheikh, Behzadi, & Salehi, ), decision‐making (Hashemi, Pilevar, & Rafeh, ; Li, Yang, & Cao, ; Özkan & İnal, ) and evaluation (Eldessouki & Hassan, ; Maher, Sarhan, Barzani, & Hamdi, ; Sangaiah, Thangavelu, Gao, Anbazhagan, & Durai, ; Sun, Hu, Lei, Zhu, & Jiang, ). For example, Sun et al () applied the ANFIS method to evaluate the ground source heat pump (GSHP) system, and found that it provided high accuracy and reliability for calculating performance indexes of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since then, the ANFIS method has been widely used in many research areas, such as prediction (Abdulshahed, Longstaff, & Fletcher, ; Hegde & Raju, ; Petković, Shamshirband, Abbasi, Kiani, & Al‐Shammari, ; Rai, Pai, & Rao, ), knowledge discovery (Huang, Tsou, & Lee, ; Inyang & Akinyokun, ; Vahidnia, Alesheikh, Behzadi, & Salehi, ), decision‐making (Hashemi, Pilevar, & Rafeh, ; Li, Yang, & Cao, ; Özkan & İnal, ) and evaluation (Eldessouki & Hassan, ; Maher, Sarhan, Barzani, & Hamdi, ; Sangaiah, Thangavelu, Gao, Anbazhagan, & Durai, ; Sun, Hu, Lei, Zhu, & Jiang, ). For example, Sun et al () applied the ANFIS method to evaluate the ground source heat pump (GSHP) system, and found that it provided high accuracy and reliability for calculating performance indexes of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on this method, threshold value will be between 0 and 1. After achieving this value we can segment an image based on it [11]. The main morphological operations are dilation, erosion, closing, opening and the hit-or-miss transform.…”
Section: Histogram Equalizationmentioning
confidence: 99%
“…These slices are few millimeters apart. Recent technical advances in CT scan increase the effectiveness and speed by taking continuous pictures of body so that there is no gape in the pictures collected [31][32][33][34][35]. Some CT images are shown in figure 6 below.…”
Section: A Spect Artifactsmentioning
confidence: 99%